Laure‑Anne Caraty, Réception et étude de la poésie lyrique médiévale de langue d'oc au siècle des Lumières : œuvres et manuscrits de La Curne de Sainte‑Palaye - Laure‑Anne Caraty (Perspectives Médiévales, 2024)
My thesis proposes to fill a gap in the literary history of the troubadours by studying in detail the work of the Parisian scholar Sainte-Palaye, that is all the manuscripts that enabled him to work on the troubadours. My aim is to determine what turning point this scholar's work represents in the reception of troubadours under the Ancien Régime, despite the oblivion into which his contribution has fallen because of the publication of Millot's Histoire littéraire des troubadours (an abbot more concerned with preserving readers' morals than with making the fin'amor known through texts). Thanks to the annotations written by Sainte-Palaye in the margins of his manuscripts, I can follow step by step the work he carried out in several disciplines: philology, linguistics, literature and translation. I tried to determine how this non-Occitan academician of the Enlightenment considered this ancient medieval poetic text.